2013
DOI: 10.1186/1471-2407-13-230
|View full text |Cite
|
Sign up to set email alerts
|

Standard or hypofractionated radiotherapy in the postoperative treatment of breast cancer: a retrospective analysis of acute skin toxicity and dose inhomogeneities

Abstract: BackgroundTo identify predictive factors of radiation-induced skin toxicity in breast cancer patients by the analysis of dosimetric and clinical factors.Methods339 patients treated between January 2007 and December 2010 are included in the present analysis. Whole breast irradiation was delivered with Conventional Fractionation (CF) (50Gy, 2.0/day, 25 fractions) and moderate Hypofractionated Schedule (HS) (44Gy, 2.75Gy/day, 16 fractions) followed by tumour bed boost. The impact of patient clinical features, sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 25 publications
8
45
0
2
Order By: Relevance
“…Furthermore, uncertainty in TLD devices, which is typically 3% to 5%, may also attribute to this disagreement. The results suggest that the TPS may be a reliable and simple alternative method for estimating the highest skin doses in breast and axillary areas to predict the location of skin reactions, based on the findings of Tortorelli et al 19 Stratified analyses revealed that the consistency between the 2 methods in the axillary and breast areas was limited only in younger patients; older patients may have more creases over their breast and axillary areas, which may increase the uncertainity of dose measurement when the TLD is used. The consistency between the 2 methods in the axillary and breast areas was limited only to the maximum dose near the skin.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Furthermore, uncertainty in TLD devices, which is typically 3% to 5%, may also attribute to this disagreement. The results suggest that the TPS may be a reliable and simple alternative method for estimating the highest skin doses in breast and axillary areas to predict the location of skin reactions, based on the findings of Tortorelli et al 19 Stratified analyses revealed that the consistency between the 2 methods in the axillary and breast areas was limited only in younger patients; older patients may have more creases over their breast and axillary areas, which may increase the uncertainity of dose measurement when the TLD is used. The consistency between the 2 methods in the axillary and breast areas was limited only to the maximum dose near the skin.…”
Section: Discussionmentioning
confidence: 91%
“…10,16,17 The total radiation dose, dose per fraction, overall treatment time, beam type and energy, and the surface area of the skin that is exposed to radiation contribute to the skin reaction. 18 Tortorelli et al 19 observed a strong correlation between areas close to the skin surface, with inhomogeneities 4107% of the prescribed dose, and desquamation areas. In a previous study, we evaluated the location consistency of moist desquamation and high-skin dose areas in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Dane z literatury potwierdzają zależność pomię-dzy nasileniem reakcji ze strony skóry a stopniem niehomogenności dawki w napromienianej piersi, szczególnie jeśli obejmowała tkanki położone tuż pod skórą. Parametr dozymetryczny V > 107% okazał się być niezależnym czynnikiem ryzyka ostrych reakcji popromiennych ze strony skóry [11]. Wiele pytań dotyczących hipofrakcjonowanej radioterapii wymaga odpowiedzi.…”
Section: Invited Commentaryunclassified